Utilizing Cocoa Rind as Organic Fertilizer to Support Sustainable Agriculture - Ramadhani Chaniago; Winarto Ramlan (UNIVERSITY OF LAMPUNG, 2016)
The main key in choosing manure is the level of ripeness, the ratio of Carbon and Nitrogen (C/N) and the Nitrogen, Phosphorus, Potassium (NPPt) contents. So far, the farmers have not effectively utilized organic materials as fertilizers in agricultural lands. Organic materials which can be used include agricultural waste and animal waste. The existence of alternative fertilizers and in order to support the development of sustainable agriculture, utilizing agricultural waste as the materials to make organic fertilizers is encouraged. Organic fertilizers can be in the forms of manure, compost, and the combination of both. The research was aimed to study the NPPt content in compost from cocoa rind and cow waste. This research was done in May – September 2015 in Sub-district Luwuk, District Banggai and in the Laboratory of Chemistry and Soil Fertility, Department of Soil Science Faculty of Agriculture, Hasanuddin University, Makassar. The experiment was conducted in a Completely Randomized Design (CRD). The experiment contained one factor with three treatments, which were repeated 3 times; thus, there were 9 treatments units. The treatments were comparison dosages of cocoa rind and cow waste, i.e. P1 = 50 kg of cocoa rind : 10 kg of cow waste; P2 = 50 kg of cocoa rind : 20 kg cow of waste; P3 = 50 kg of cocoa rind : 30 kg of cow waste. Data were analysed by comparing the average of NPPt element in cocoa rind compost and cow waste. Data was then analyzed statistically by One Way Anova (One Way Variant Analysis) by using SPSS 19.0 for Windows and further analyzed by Least Significant Difference (LSD) 1% by using Microsoft Excel Windows 7. The results showed that the highest macro nutrients content was in P2 with N = 0.25%; P = 3.91%; K = 5.23% and the lowest was in P3 with N = 0.19% and P = 3.33% as well as in P1 with K = 4.16%.Keywords: Agricultural waste, compost, cow waste [How to Cite: Ramadhani C and W Ramlan. 2016. Utilizing Cocoa Rind as Organic Fertilizer to Support Sustainable Agriculture. J Trop Soils 21: 33-39. Doi: 10.5400/jts.2016.21.1.33]